The Synthesis Method of Intermetallic Alloys Based on Ti–Cr with C14 and C36 Laves Phases for Hydrogen Storage; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 13, iss. 1 - Murashkina T. L. Tatiana Leonidovna; Syrtanov M. S. Maksim Sergeevich; Shabunin A. S. Artem Sergeevich; Laptev R. S. Roman Sergeevich (2019, 2019)
Title screen